Konsep Kesadaran Digital Perspektif Psikologi Transpersonal dan Relevansinya terhadap Pembentukan Spiritualitas - Jimmy Saputra Az; Konto Iskandar Dinata (Al-Kindi, 2025)
The rapid development of digital technology has profoundly impacted human consciousness, bringing with it positive impacts such as expanded access to information, as well as negative challenges such as attention deficit disorder and spiritual crisis. This article aims to propose a holistic concept of digital consciousness by integrating a transpersonal psychology perspective, which emphasizes the spiritual dimension and awareness beyond the ego. Through a literature review, this study concludes that combining transpersonal psychology principles with reflective technology use, such as mindfulness apps, digital journals, and digital decluttering practices, can transform technology from a mere entertainment tool to a partner in self-development. Thus, true digital consciousness is not simply about technological proficiency, but about a new paradigm that integrates technical sophistication, spiritual growth, and ethical practices to achieve holistic human well-being in the digital age